A Theoretical Investigation of Charge Transfer Dynamics from Sensitized Molecule D35CPDT Dye to SnO_2 and TiO_2 Semiconductor - Hasan, Estabraq; Alagealy, Hadi J. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
In this research, the dynamics process of charge transfer from the sensitized D35CPDT dye to tin(iv) oxide( ) or titanium dioxide ( ) semiconductors are carried out by using a quantum model for charge transfer. Different chemical solvents Pyridine, 2-Methoxyethanol. Ethanol, Acetonitrile, and Methanol have been used with both systems as polar media surrounded the systems. The rate for charge transfer from photo-excitation D35CPDTdye and injection into the conduction band of or semiconductors vary from a to for system and from a to for the system, depending on the charge transfer parameters strength coupling, free energy, potential of donor and acceptor in the system. The charge transfer rate in D35CPDT / the system is larger than the rate in D35CPDT/ a system depending on transition energy and driving energy. However, the charge transfer for both systems to be large is associated with large transition energy, decreasing driving energy and potential, and increasing strength coupling with Methanol solvent.